Melaleuca entrapping microsites as a nature based solution to coastal erosion: A pilot study in Kien Giang, Vietnam. (1st April 2018) - Nguyen, T.P.
Abstract: Accumulation of fine grained sediment and natural regeneration of mangrove species are normally prioritized to control erosion on mangrove dominated muddy coasts. Current solutions to manage eroded mangrove dominated muddy coasts have been not as cost-effective as expected. Entrapping microsites, although mainly used for restoring eroded terrestrial resources, were first tested for restoring an eroded mangrove dominated muddy coast of Vam Ray, Hon Dat, Kien Giang, Vietnam. Entrapping microsites, constructed with a 50 cm layer of discarded Melaleuca small sticks that were overlain on the surface of the site, accumulated a high level of fine grained sediment and promoted robust natural regeneration or regrowth of local mangrove species after approximately two years. The effectiveness and efficiency of the Vam Ray Melaleuca entrapping microsites provide a good basis on which further research and ground works can proceed. Highlights: Entrapping microsites were constructed using discarded Melaleuca small sticks. The Melaleuca entrapping microsites were effective in stabilizing eroded coastal area. The Melaleuca entrapping microsites provide a good basis for further research works.